The growth of juvenile jaguar guapote (Cichlasoma managuense) fed diets with different carbohydrate levels (ESP) - Ulloa R., Juan B. (1995)
The experiment was conducted in a 16 45 L aquaria recirculation system. The objective was to evaluate the growth of jaguar guapote (Cichlasoma managuense) when fed isocaloric diets with increasing carbohydrate levels from 11 to 36 percent. Relative metabolic growth rate and feed conversion were similar with diets containing 11.5%, 18.8% and 26.5% carbohydrate (P > 0.05) . The highest protein efficiency ratio (PER) and apparent net protein utilization (NPUa) values were found with the 18.8% carbohydrate diet. Growth performance, feed utilization parameters and the survival were the lowest with fish fed the highest carbohydrate level (35.6%). Fish body protein increased and body fat decreased with increasing dietary carbohydrate levels. The body ash showed a trend similar to the body protein. It is concluded that juvenile C. managuense can grow well when fed 40% protein diets containing up to 26.5% carbohydrate.